2020
DOI: 10.7554/elife.54348
|View full text |Cite
|
Sign up to set email alerts
|

Topological constraints in early multicellularity favor reproductive division of labor

Abstract: Reproductive division of labor (e.g., germ-soma specialization) is a hallmark of the evolution of multicellularity, signifying the emergence of a new type of individual and facilitating the evolution of increased organismal complexity. A large body of work from evolutionary biology, economics, and ecology has shown that specialization is beneficial when further division of labor produces an accelerating increase in absolute productivity (i.e., productivity is a convex function of specialization). Here we show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 75 publications
1
46
2
1
Order By: Relevance
“…Many of the major conceptual topics surrounding the evolution of multicellularity fall under this category. These include: (i) how multicellular groups form and become Darwinian units capable of adaptation [ 18 , 29 , 30 , 31 , 32 , 33 ], (ii) how the transition to multicellularity affects subsequent evolutionary processes [ 6 , 34 ], (iii) how cooperative behaviors associated with complex multicellular organisms (e.g., cellular differentiation) evolve and remain stable in the face of social defection [ 35 , 36 , 37 , 38 , 39 , 40 ], (iv) how multicellular life cycles arise and shape the subsequent evolution of multicellularity [ 13 , 14 , 41 ], and (v) how multicellular lineages co-opt and modify traits of their unicellular ancestor for novel multicellular purposes [ 21 , 27 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the major conceptual topics surrounding the evolution of multicellularity fall under this category. These include: (i) how multicellular groups form and become Darwinian units capable of adaptation [ 18 , 29 , 30 , 31 , 32 , 33 ], (ii) how the transition to multicellularity affects subsequent evolutionary processes [ 6 , 34 ], (iii) how cooperative behaviors associated with complex multicellular organisms (e.g., cellular differentiation) evolve and remain stable in the face of social defection [ 35 , 36 , 37 , 38 , 39 , 40 ], (iv) how multicellular life cycles arise and shape the subsequent evolution of multicellularity [ 13 , 14 , 41 ], and (v) how multicellular lineages co-opt and modify traits of their unicellular ancestor for novel multicellular purposes [ 21 , 27 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can ‘come together’ via aggregation or ‘stay together’ by failing to separate after reproduction [ 51 ]. In this paper, we focus on multicellular organisms that form by ‘staying together’ because it is a common mode of multicellular development [ 45 ]; it favors the evolution of cooperation [ 52 ] and cellular differentiation [ 37 ]; and all ‘complex’ multicellular organisms (i.e., animals, plants, red algae, brown algae, and fungi) grow through cell adhesion following cell reproduction [ 53 ]. If multicellularity evolves via cells staying together, then the physical connection between cells must be maintained, at least until the multicellular organism fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Consider a one-dimensional chain of cells, as examined by Yanni et al Chains are found in species like cyanobacteria that form filaments of cells, and such structures might have been important at the onset of the evolution of multicellularity (Figure 4B) (Yanni et al, 2020). We assume arbitrarily that "odd" cells along the filament are putative helpers and "even" cells are putative reproductives.…”
Section: (B) Can Topological Constraints Lead To Division Of Labour By Reciprocal Specialisation?mentioning
confidence: 99%
“…The establishment and maintenance of germ cells are critical for ensuring the survival of a species [ 1 ]. Many factors affect germ cell maintenance, with temperature being a major factor [ 2 , 3 ]. Male germ cells (sperm) are produced through the complex process of spermatogenesis in the scrotum, where the temperature is lower than the core body temperature of most male mammals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…a,b Means in same column with different superscripts differ (p < 0.05 to p < 0.001) 1. Significant different expression of PCNA vs. apoptosis of germ cells in preweaning, cryptorchid, and contrascrotal testes (p < 0.05) 2. Significantly different expression of PCNA vs. apoptosis of germ cells in preweaning, cryptorchid, and contrascrotal testes (p < 0.01) 3.…”
mentioning
confidence: 99%